Adults who Smoke Should Have Pulmonary Function Testing Before and After Coronary Artery Bypass Grafting (CABG) - PhD, Maqdad Taaqi; PhD, Hesham N Alrowayeh; PhD, Sameera H Aljadi; PhD, Hanan Ahmad Alfadhli (South Eastern European Journal of Public Health, 2024)
Background: Recent research has shown that coronary artery bypass grafting (CABG) has a mortality rate of 0.6–3.0%, making it a popular and generally safe cardiac operation. The purpose of this study is to examine the relationship between sex, age, and diabetes in the early changes in lung volumes measured by pulmonary function tests before and after coronary artery bypass grafting (CABG) in individuals who smoke. Subjects and procedures: Elective coronary artery bypass surgery was the procedure of choice for 200 consecutive patients in this prospective controlled trial. Participants who were not part of the trial were those who were in an emergency or who had a valve operation done alongside a CABG procedure. Based on the data from the operation, the cardiopulmonary bypass time was 98.89 minutes with a standard deviation of 25.14 minutes. The average time for cardiac ischemia was 67.8 minutes with a standard deviation of 26.6 minutes and a range of 25 to 227 minutes. The total time spent in the intensive care unit was 53.54 hours with a standard deviation of 27.98 hours and a range of 4 to 102 hours. Thirteen patients, or 6.5%, were cold, while the remaining patients were warm. Thirteen patients, or 6.5%, used ice slush as a topical cooling method. The results of the pulmonary function tests taken before and after surgery were significantly different. Conclusion: Postoperative obstructive and restrictive breathing problems are associated with cigarette smoking's detrimental effects on pulmonary functioning. Patients with a smoking history who are scheduled for elective revascularization surgery should have their pulmonary status evaluated before surgery, and they should be strongly encouraged to quit smoking as soon as possible before surgery to minimize the risk of respiratory complications after surgery.